Efecto del uso del suelo sobre las formas de fósforo de un Andisol - Henríquez Henríquez, Carlos Roberto (2015)
The effect of agricultural land use on the forms of P in a Typic Hapludand was evaluated. An area of 8.4 ha composed of 3 adjacent lots, dedicated for over 20 years to secondary forest and plantings of sugarcane and coffee, was chosen at Juan Viñas, Costa Rica. Soil samples were taken using an 8x6 grid layout of sampling points, spaced at 40 m. Soil samples were analyzed with the P fractionation methodology proposed by Hedley et ál. (1982). Total P varied between 936 and 2516 mg.kg-1. Both coffee and sugar cane lots (1934 y 1754 mg.kg-1 respectively), showed the highest values of total-P compared with the forest (1419 mg.kg-1), suggesting a positive overall balance of P due to its accumulation through the years. The coffee area showed the highest values of P-labile and P-sesquioxides-Fe/Al, which was related to usual higher fertilization compared with areas of sugarcane and forest. The greatest value of P-residual was found in sugarcane with almost 48% of total P. The P-organic varied 27 to 29% of the total suggesting its importance as valuable sink of P. We conclude that the type of land use had a significant effect on the forms of P which was observed in both the quantity and distribution of different forms of P in soil.